Oral symptoms leading to diagnosis of sarcoidosis - MAHESH, D.R. (International Arab Journal of Dentistry (IAJD), 2012)
Sarcoidosis is a multisystemic granulomatous disease of unknown etiology that may manifest in the oral and maxillofacial region. Enlargement of the major salivary glands may be the first identifiable sign of this condition, which is often characterized by a variety of nonspecific symptoms. In this report, we present the case of a patient suffering from xerostomia, dysgeusia, burning sensation, xerophthalmia and bilateral parotid gland enlargement. The diagnosis of systemic sarcoidosis was established, based on the clinical associated symptoms as well as the histopathologic results of a biopsy of labial minor salivary glands.